2020
DOI: 10.18178/ijeee.8.2.24-30
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Natural Circulation in a Single-Phase Loop with Different Widths

Abstract: The natural circulation loop is one of the design concepts of a cooling system in new advanced reactors that has attracted many researchers to develop it. This study aimed to perceive the effect of horizontal width variation on the thermal behavior of a single-phase Natural Circulation Loop (NCL). NCL apparatus with a vertical heater and a vertical cooler was designed for experimental study. The height of the loop was 100 cm while the width of the loop was varied at 50 cm and 100 cm. The heater was designed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The effect of vertical height on the natural circulation loop (NCL) with vertical heater and horizontal cooler orientation has been reported in paper [8]. Then, the authors' work has been done on paper [9], demonstrated experimentally that expansion tank placement is crucial in single-phase NCLs. Also, subsequent work by experimental and modelling showed that loop geometry could affect natural circulation-based cooling systems [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of vertical height on the natural circulation loop (NCL) with vertical heater and horizontal cooler orientation has been reported in paper [8]. Then, the authors' work has been done on paper [9], demonstrated experimentally that expansion tank placement is crucial in single-phase NCLs. Also, subsequent work by experimental and modelling showed that loop geometry could affect natural circulation-based cooling systems [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the authors' work has been done on paper [9], demonstrated experimentally that expansion tank placement is crucial in single-phase NCLs. Also, subsequent work by experimental and modelling showed that loop geometry could affect natural circulation-based cooling systems [9][10][11][12]. These studies revealed that the instability of the NCL is influenced by the loop geometry.…”
Section: Introductionmentioning
confidence: 99%